(untitled) (LEARNing Landscapes, 2020)
Why aren’t English teachers creative writers? Why is there little to no emphasis on creative writing in ELA classes? What are the implications of popular media portrayals of the writer on students’ perception of writing? In my classroom practice, I encouraged a variety of writing styles that allowed students to grow as readers, but, more importantly, as writers. This paper attempts to understand how we can integrate creative writing with traditional academic writing, to imagine its possibilities, and to examine how we can do more of it.